2016
DOI: 10.1111/jdi.12466
|View full text |Cite
|
Sign up to set email alerts
|

Is GLP‐1 a hormone: Whether and When?

Abstract: Glucagon‐like peptide‐1 (GLP‐1) is a product of proglucagon cleavage synthesized in L cells in the intestinal mucosa, α‐cells in the pancreatic islet, and neurons in the nucleus of the solitary tract. GLP‐1 is essential for normal glucose tolerance and acts through a specific GLP‐1 receptor that is expressed by islet β‐cells as well as other cell types. Because plasma concentrations of GLP‐1 increase following meal ingestion it has been generally presumed that GLP‐1 acts as a hormone, communicating information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 52 publications
0
76
0
Order By: Relevance
“…The role of exenatide in suppressing appetite and inducing glucose‐stimulated insulin secretion is well documented . The current study identifies a novel positive effect of exenatide on insulin clearance in parallel with insulin secretion to prevent chronic hyperinsulinemia and the subsequent increase in hepatic de novo lipogenesis …”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The role of exenatide in suppressing appetite and inducing glucose‐stimulated insulin secretion is well documented . The current study identifies a novel positive effect of exenatide on insulin clearance in parallel with insulin secretion to prevent chronic hyperinsulinemia and the subsequent increase in hepatic de novo lipogenesis …”
Section: Discussionmentioning
confidence: 85%
“…(B) mRNA levels of (i) hGLP‐1R , (ii) hCEACAM1 ( hCC1 ), (iii) hPPAR α, and (iv) hPPAR γ were analyzed in HepG2 as above except for pre‐incubation with exendin 9‐39 (dark gray). * P < 0.05 versus S, † P < 0.05 Ex + exendin 9‐39 (Ex+ ) versus Ex alone. Abbreviations: Ex, exenatide; Ex , exendin fragment 9‐39; h, human; GAPDH, glyceraldehyde‐3‐phosphate dehydrogenase; /GAPDH, normalized to GAPDH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our principal target of the NPs is the glucagon‐like peptide 1 receptor (GLP‐1R) which is expressed on the membranes of beta cells and has an important role in the regulation of insulin secretion . The natural ligand, glucagon‐like peptide‐1 (GLP‐1) binds to the GLP1‐R with high affinity, but its half‐life in vivo is very short for the fine regulation of blood sugar level . Current therapeutic approaches have utilized mimetics of GLP‐1, most notably exenatide, the synthetic form of the naturally occurring peptide exendin‐4 (Ex4) …”
Section: Development and Testing Of Nanomaterials For Multimodality Ementioning
confidence: 99%
“…Although this has been established for some GI hormones, this view has now been challenged for others. For example, GLP-1 which is synthesized in the distal small intestine and colon is potently inactivated by the proteolytic enzyme dipeptidyl peptidase-4 (DPP-4) and further inactivated in the liver so that by the time it reaches the arterial circulation, its concentration is so low that it may not be sufficient to activate islet cell GLP-1 receptors [27, 28]. This observation has raised serious doubts about the endocrine model of GLP-1 and suggested that most of the physiological functions of GLP-1 secreted from enteroendocrine cells may be mediated through direct activation of enteric sensory nerve endings [29].…”
Section: Enteric Nervous System and The Gut Connectomementioning
confidence: 99%